2015
DOI: 10.3168/jds.2015-9866
|View full text |Cite
|
Sign up to set email alerts
|

Association of bedding types with management practices and indicators of milk quality on larger Wisconsin dairy farms

Abstract: The objective of this study was to identify associations of bedding type and selected management practices with bulk milk quality and productivity of larger Wisconsin dairy farms. Dairy herds (n=325) producing ≥11,340 kg of milk daily were surveyed during a single farm visit. Monthly bulk milk SCC and total bacteria counts were obtained from milk buyers for 255 farms for a 2-yr period. Of farms with the same type of bedding in all pens during the study period, most used inorganic bedding (IB), followed by orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
46
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 48 publications
11
46
1
1
Order By: Relevance
“…This result corroborates that of Bradley et al (2018) who showed that the bedding type (not composted RMS, sand, and sawdust) did not affect the total bacterial count in bulk tank milk, even though counts in the bedding material itself were higher when RMS was used, compared with sand or sawdust. Rowbotham and Ruegg (2015) found similar results. In their study comparing the following bedding materials: inorganic, organic nonmanure, and manure-based, no association was observed between total bacterial count in bulk tank milk and bedding type.…”
Section: Discussionsupporting
confidence: 62%
“…This result corroborates that of Bradley et al (2018) who showed that the bedding type (not composted RMS, sand, and sawdust) did not affect the total bacterial count in bulk tank milk, even though counts in the bedding material itself were higher when RMS was used, compared with sand or sawdust. Rowbotham and Ruegg (2015) found similar results. In their study comparing the following bedding materials: inorganic, organic nonmanure, and manure-based, no association was observed between total bacterial count in bulk tank milk and bedding type.…”
Section: Discussionsupporting
confidence: 62%
“…Cows in the UW research herd had similar demographic characteristics and were exposed to management practices that were typical of modern conventional dairy farms in the same region (Rowbotham and Ruegg, 2015). Both milk production and SCC of enrolled cows were similar to those of commercial herds located in Wisconsin (Pinzón-Sánchez and Fuenzalida et al, 2015;Rowbotham and Ruegg, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These differences in bedding materials may lead to differences in manure VS which may in turn affect CH 4 emissions. Many considerations influence the selection of bedding materials beyond availability including cost, barn design, cow health, and cow comfort (Norring et al 2008;Sheppard et al 2011;Husfeldt et al 2012;Rowbotham and Ruegg 2015). Overwhelmingly, inorganic bedding (i.e., sand) maintains better herd health (Norring et al 2008) as well as harbouring fewer bacteria than organic materials such as wood shavings and straw (Hogan et al 1989;Eckes et al 2001;Bey and Reneau 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, farms employing inorganic bedding have exhibited higher milk production than those employing other bedding types (Godden et al 2008). If dairy operation transitions away from more traditional organic bedding as a result of the lower costs (Rowbotham and Ruegg 2015) and these other positive attributes (Husfeldt et al 2012), it is important to consider the impact that this may have on GHG emissions.…”
Section: Introductionmentioning
confidence: 99%